Analisis Kemampuan Berpikir Logis dengan Menggunakan Metode Pembelajaran Accelerated Learning (AL) - Dwi Maulida Sari; Diyah Hoiriyah (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2020)
The aim of this article is to analyze students’ mathematical logical thinking ability where accelerated learning model been applied. Research is conducted in fifth semester in one of universities in Asahan. It was found that the n-gain mean of mathematical logical thinking ability of class AL students was included in the high category improvement as stated by Hake's n-gain improvement criteria. The class AL standard deviation value shows that the distribution of the n-gain value data varies widely. This shows that the Accelerated learning (AL) learning model can be used as a model that can improve logical thinking skills.